The Sugarcane Complex in Brazil: The Role of Innovation in a Dynamic Sector on Its Path Towards Sustainability - Rengifo, Gustavo Adolfo Corrêa (The International Journal of Sociology of Agriculture and Food, 2018)
There is great concern at present about obtaining energy for the development of humanity. Non-renewable energy resources are being depleted, and we are looking urgently to replace non-renewable rainforest wood and other slow-recovering energy resources, without the intensive use of fossil fuels. Recently, biofuels have appeared as a viable alternative due to their renewability, relative ease of production and low impact on the environment. One of the most important biofuels is ethanol, produced mainly from corn and sugarcane. The latter is used most, especially in developing countries, and Brazil is at the head of world producers of sugarcane. Brazil is the world’s leading producer of sugar and second in ethanol from sugarcane. Generally, when Brazil is named, it is thought of in terms of sugarcane and its products, tropical climate and sustainability. Sustainability is the main concern for Brazil, and it is here that a question emerges: will sugarcane crops be sustainable in the future?